A Better Tenure Battle: Fighting Bias in Teaching Evaluations - Deo, Meera E. (Columbia Journal of Gender and Law, 2015)
As legal education undergoes significant changes with regard to both student enrollment and faculty hiring, the fight to keep law faculty tenure is at the forefront. But the focus on tenure should be about the standards themselves. A better approach would be to change tenure requirements to create a more just and inclusive set of standards and criteria for evaluation. This Article draws from the first systematic, comprehensive, mixed-method empirical law faculty diversity study to investigate how challenges in the classroom and bias in teaching evaluations affect female law faculty of color. The in-depth interviews of female law faculty of color are systematically analyzed using Atlas.ti software, finding that students directly challenge particular faculty in class, sometimes through verbal and even physical abuse, and write insensitive and irrelevant race- and gender-based comments on anonymous teaching evaluations. These encounters often have negative effects on the professional trajectory of women of color law professors, most notably when these individuals seek promotion and tenure. Instead of supporting these discriminatory barriers to advancement, legal institutions should do away with student evaluations altogether, modify them, or supplement them with more rigorous and less discriminatory forms of evaluation. This is the way to fight bias in teaching evaluations.